0003 LGI1 and CASPR2 Autoimmunity: Sleep Symptoms, Polysomnography, and Quantitative REM Sleep without Atonia. (27th May 2020) - Devine, M F; Feemster, J C; Lieske, E A; McCarter, S J; Sandness, D J; Steele, T; Boeve, B F; Silber, M H; McKeon, A; St. Louis, E K
Abstract: Introduction: Sleep disturbances, including rapid eye movement (REM) behavior disorder (RBD), are known manifestations of voltage-gated-potassium-channel-complex VGKC-IgG seropositivity (VGKC+). Discovery of leucine-rich, glioma inactivated protein 1 (LGI1) and contactin-associated protein 2 (CASPR2) have refined our understanding of VGKC+. VGKC+ without LGI1/CASPR2-IgG ("double-negative") has lost its clinical significance. Previous detailed sleep analysis of these subtypes has been limited. Methods: We performed a retrospective study to characterize clinical and polysomnographic features of LGI1/CASPR2 seropositive (LGI1+/CASPR2+) and VGKC double-negative patients, including quantitative REM sleep without atonia (RSWA). Quantified RSWA was compared to matched controls and normative RSWA percentiles. Results: Eleven LGI1+/CASPR2+ (LGI1+, 9) and twelve VGKC double-negative patients were analyzed. Insomnia was seen in 55% of LGI1+/CASPR2+ and 8% of VGKC double-negative patients (p=0.05). The LGI1+/CASPR2+ group had reduced slow wave sleep compared to the VGKC double-negative group. Five LGI1+ patients had clinical dream enactment behavior (DEB). Eight LGI1+ patients met quantitative diagnostic levels of RSWA. Higher RSWA levels were seen in the LGI1+/CASPR2+ group. Ten LGI1+/CASPR2+ patients received immunotherapy; all ten neurologically benefited with sleep benefits in 6/10. Conclusion: Sleep disorders such as insomnia and RBD are part of the LGI1/CASPR2 autoimmune phenotype. Objective sleep manifestations can be seen on polysomnogram in the form of reduced N3 and elevated RSWA as compared to controls. Quantitative RSWA analysis identified RBD in more LGI1+ patients than clinical report or qualitative RSWA. In this study, RBD was only seen with LGI1+, not CASPR2+. The intermediate RSWA levels of the VGKC double-negative patients may suggest a spectrum of abnormal motor activity in these related antibodies. Additional studies are needed to further explore the biomarker potential of quantitative RSWA in autoimmune neurological conditions. Support: This project was supported by the National Center forResearch Resources, National Institutes of Health, through Grant Number 1 UL1 RR024150- 01.